Factors associated with alcohol use before sex among HIV-negative female sex workers in Zambia. (February 2020) - Malama, Kalonde; Sagaon-Teyssier, Luis; Parker, Rachel; Tichacek, Amanda; Sharkey, Tyronza; Kilembe, William; Inambao, Mubiana; Price, Matt A; Spire, Bruno; Allen, Susan
Female sex workers (FSWs) are at high risk of HIV infection. Alcohol use prior to sex can compound this risk. We investigated the factors associated with having sex under the influence of alcohol among Zambian FSWs. Community health workers and peer FSWs recruited 331 HIV-negative FSWs in Lusaka and Ndola. In a cross-sectional survey, we asked FSWs how often they had sex under the influence of alcohol in the previous month and categorised responses as 'always' and 'not always'. The adjusted odds ratios (AORs) of always having sex under the influence of alcohol were higher among FSWs who charged clients medium (AOR: 2.20, 95% confidence interval [CI]: 1.04–4.68) and low fees (AOR: 2.65, 95% CI: 1.26–5.60) for sex versus high fees; received 9–19 (AOR: 2.37, 95% CI: 1.15–4.91) and 20 or more clients per month (AOR: 3.06, 95% CI: 1.47–6.37) versus up to 8 clients per month; and never used condoms versus always used condoms with clients (AOR: 4.21, 95% CI: 1.53–11.55). FSWs who always used alcohol before sex appeared more likely to engage in riskier sex and charge clients lower fees. Interventions for financial empowerment and alcohol risk reduction should complement existing HIV prevention interventions for FSWs.